Hydrogen storage material, hydrogen storage container, and hydrogen supply device
Patent Information
- Application Number
- CN202280029481.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-04-26
- Filing Date
- 2022-04-25
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-04-25
AI Technical Summary
但是,在这样的环境下工作的储氢合金的报告例少
[0020] The hydrogen storage material of the present invention has excellent hydrogen absorption and release characteristics below 0°C due to its alloy composition with the above-mentioned specific elements, and is suitable for use in hydrogen storage applications.
Smart Images

Figure CN117222768B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to hydrogen storage materials, hydrogen storage containers, and hydrogen supply devices. Background Technology
[0002] Hydrogen storage alloys are alloys capable of reversibly absorbing and releasing hydrogen. They have already been used as negative electrode materials in nickel-metal hydride batteries. However, in recent years, they have also gained attention as materials for the safe storage of hydrogen, which is of great interest as an energy source, and their application in hydrogen storage and supply systems is under continuous research. Hydrogen storage alloys include various types such as AB5, AB2, TiFe, TiVCr, and other BCC types. Among them, AB5 alloys are easy to initially activate and have relatively good plateau characteristics in their hydrogen pressure-composition isotherm curves (PCT curves), thus they are being researched towards practical application as hydrogen storage materials.
[0003] It is anticipated that the application environments for hydrogen storage materials will become increasingly diverse in the future. Currently, typical hydrogen storage tanks absorb hydrogen near room temperature and raise the temperature to a maximum of approximately 100°C when using the hydrogen, operating at hydrogen release pressures below 10 atmospheres. However, future applications are envisioned in cryogenic regions below 0°C, such as liquefied hydrogen boiling gas recovery and hydrogen storage in cold areas, or in applications requiring high release pressures above 10 atmospheres at room temperature (e.g., hydrogen compressor applications). However, there are few reports of hydrogen storage alloys operating in such environments. Furthermore, alloys that exhibit good initial activation while simultaneously meeting requirements for high hydrogen absorption capacity, good plateau flatness, and hysteresis are extremely rare.
[0004] Patent document 1 discloses: (1) a hydrogen storage material of the following composition, wherein the hydrogen storage material is composed of a general formula LmNi a-x A x (where Lm is a rare earth metal containing 40%–70% La, 0.1%–2.0% Ce, and metals such as Nd, Pr, and Sm; A is a metal selected from the group consisting of Al, Mn, Fe, and Cr; a is an alloy represented by the formula 4.8 < a < 5.5, x = 0.01–2.0); and (2) the following hydrogen storage material, wherein the hydrogen storage material is composed of a material of the general formula LmNi a-x A y B z(In the formula, Lm is a rare earth metal containing 40%–70% La, 0.1%–20% Ce, and metals such as Nd, Pr, and Sm; A is a metal selected from the group consisting of Al, Mn, and Fe; B is a metal selected from the group consisting of Mn (except when A is Mn), Co, Zr, and V; a is 4.8 < a < 5.5, x = y + z, y and z = 0.01–2.0) This describes an alloy composition. Furthermore, it is disclosed that by adopting the above composition, a hydrogen storage material can be obtained that is easily activated at room temperature, has a large hydrogen absorption capacity, a fast absorption and release rate, low hysteresis, and a flat plateau.
[0005] Patent document 2 discloses: (1) a hydrogen storage material of the following characteristics, wherein the hydrogen storage material is composed of the general formula R·Ni 5-(a+b+c) ·A a ·B b ·Co c (where R is a rare earth metal or a mixture of rare earth metals; A is one of Mn, Fe, and Cr; B is one of Al and Sn; a, b, and c are each 0.01 to 1.0) represents a hydrogen storage material containing one of Al or Sn and Co; (2) the following hydrogen storage material, characterized in that the hydrogen storage material is composed of the general formula R·Ni 5-(a+b+c+d) ·A a ·B b ·C c ·Co d (Where R is a rare earth metal or a mixture of rare earth metals; A and B are each one of Mn, Fe, and Cr, and A and B are different metals; C is one of Al and Sn; a, b, c, and d are each 0.01 to 1.0) indicates that it contains one of Al or Sn and Co. Furthermore, it is disclosed that by adding Co and Al or Sn together with one or two of Mn, Fe, and Cr to R-Ni alloys, the uptake is increased and the hysteresis is reduced.
[0006] Existing technical documents
[0007] Patent documents
[0008] Patent Document 1: Japanese Patent Application Publication No. 60-70154
[0009] Patent Document 2: Japanese Patent Application Publication No. 63-47345 Summary of the Invention
[0010] The problem that the invention aims to solve
[0011] Although both Patent Document 1 and Patent Document 2 improved various properties by adding elements, the envisioned operating environment is about 0°C to about 100°C. In order to use it in low-temperature environments below 0°C, it is believed that new technology development is needed.
[0012] Therefore, the objective of this invention is to provide a hydrogen storage material that exhibits suitable hydrogen absorption (storage) and release characteristics for hydrogen storage applications in low-temperature environments below 0°C. In particular, it aims to provide a hydrogen storage material with high hydrogen absorption (storage) capacity and hydrogen release capacity, capable of hydrogen absorption and release in a temperature range of -20°C, and exhibiting low hysteresis in its PCT curve. Furthermore, it aims to provide a hydrogen storage container and a hydrogen supply device having the hydrogen storage container, wherein the hydrogen storage container contains a hydrogen storage material that exhibits suitable hydrogen absorption and release characteristics for hydrogen storage applications in low-temperature environments below 0°C.
[0013] Methods for solving problems
[0014] In order to solve the above-mentioned problems, the inventors conducted in-depth research and found that an alloy with a composition based on LaNi5 and containing specific rare earth elements and transition metal elements has sufficient hydrogen storage and release capacity at -20°C. In addition to small hysteresis, the PCT curve also shows a clear squareness, so the amount of hydrogen that can be released is large, and hydrogen with almost no pressure change can be released until the end of the release period, thus completing the present invention.
[0015] That is, according to the present invention, a hydrogen storage material having an alloy composed of elements represented by the following formula (1) is provided.
[0016] La a Ce b Sm c Ni d M e (1)
[0017] [In formula (1), M is at least one selected from Mn, Co, and Al, and must include Mn. a is 0.00≤a≤0.62, b is 0.20≤b≤0.57, c is 0.17≤c≤0.60, d is 4.50≤d≤5.20, e is 0.15≤e≤0.70, a+b+c=1, c+e is 0.55≤c+e≤1.20, and d+e is 5.13≤d+e≤5.40.]
[0018] According to other aspects of the invention, a hydrogen storage container having the above-mentioned hydrogen storage material and a hydrogen supply device having the hydrogen storage container are provided.
[0019] Invention Effects
[0020] The hydrogen storage material of the present invention has excellent hydrogen absorption and release characteristics below 0°C due to its alloy composition with the above-mentioned specific elements, and is suitable for use in hydrogen storage applications. Attached Figure Description
[0021] [ Figure 1[This is a hydrogen pressure-composition isotherm (PCT curve) at -20°C for the alloy powder of Example 1 and the alloy powder of Comparative Example 1. The equilibrium pressure on the y-axis represents the hydrogen absorption pressure during hydrogen storage and the hydrogen release pressure during hydrogen release.]
[0022] [ Figure 2 [This is a hydrogen pressure-composition isotherm (PCT curve) at -20°C for the alloy powder of Example 1 and the alloy powder of Comparative Example 3. The equilibrium pressure on the y-axis represents the hydrogen absorption pressure during hydrogen absorption and the hydrogen release pressure during hydrogen release.] Detailed Implementation
[0023] The present invention will now be described in detail. The hydrogen storage material of the present invention is a material having an alloy composed of elements represented by the following formula (1). Preferably, it is a material composed of such an alloy. Hereinafter, the alloy composed of elements represented by formula (1) will sometimes be referred to as the alloy of the present invention.
[0024] La a Ce b Sm c Ni d M e (1)
[0025] [In formula (1), M is at least one selected from Mn, Co, and Al, and must include Mn. a is 0.00≤a≤0.62, b is 0.20≤b≤0.57, c is 0.17≤c≤0.60, d is 4.50≤d≤5.20, e is 0.15≤e≤0.70, a+b+c=1, c+e is 0.55≤c+e≤1.20, and d+e is 5.13≤d+e≤5.40.]
[0026] In equation (1), a, b, c, d, and e represent the proportion of each element by the ratio of atomic numbers, as detailed below. Hereinafter, this proportion will sometimes be referred to as "content" or "amount".
[0027] La is effective in increasing hydrogen uptake, and in equation (1), the La content 'a' is 0.00 ≤ a ≤ 0.62. The lower limit of 'a' is preferably 0.01 ≤ a, more preferably 0.02 ≤ a. The upper limit of 'a' is preferably a ≤ 0.40. When the value exceeds the upper limit, the equilibrium pressure may decrease.
[0028] Ce is effective for increasing equilibrium pressure, and in equation (1), the Ce content b is expressed as 0.20 ≤ b ≤ 0.57. The lower limit of b is preferably 0.22 ≤ b. If the value exceeds the upper limit, the hysteresis of the PCT curve may deteriorate.
[0029] Sm is effective in increasing the equilibrium pressure and also in showing a clear squareness in the PCT curve. In equation (1), the Sm content c is expressed as 0.17 ≤ c ≤ 0.60. As the lower limit of c, it is preferably 0.20 ≤ c, more preferably 0.22 ≤ c, and particularly preferably 0.24 ≤ c. As the upper limit of c, it is preferably c ≤ 0.55. If the value is less than the lower limit, the effect of increasing the equilibrium pressure may not be expected, and the effect of showing a clear squareness in the PCT curve may not be obtained. If the value is greater than the upper limit, the hydrogen storage capacity may decrease. It should be noted that squareness refers to the degree of shoulder shown in the shape at the end of the PCT release curve. The more defined the shoulder, the better the squareness. The alloy with good squareness shows the ability to release the stored hydrogen at a constant release pressure until the end of the release. The squareness index in this application is described later.
[0030] Ni plays an effect in improving the durability and reducing hysteresis of the hydrogen storage alloy involved in this invention. In formula (1), the d of the Ni content is 4.50 ≤ d ≤ 5.20. As the lower limit of d, it is preferably 4.55 ≤ d, and as the upper limit of d, it is preferably d ≤ 5.15. If the value is less than the lower limit, the effect of improving durability and reducing hysteresis may not be expected, and if the value is greater than the upper limit, the hydrogen storage capacity may decrease.
[0031] M is at least one element selected from Mn, Co, and Al, and must consist of elements including Mn to effectively reduce the hysteresis of the PCT curve. In equation (1), e represents the M content as 0.15 ≤ e ≤ 0.70. As a lower limit for e, it is preferably 0.17 ≤ e. If the value is less than the lower limit, the effect of reducing the hysteresis of the PCT curve may not be expected; if the value is greater than the upper limit, the equilibrium pressure and the hydrogen adsorption and release rate may decrease.
[0032] In equation (1), d+e represents the total content of Ni and M. This value affects the hysteresis and hydrogen uptake of the PCT curve of the hydrogen storage material of the present invention. By adjusting it to the following range, it is possible to produce an alloy with a small hysteresis of the PCT curve while maintaining sufficient hydrogen uptake for hydrogen storage. d+e is 5.13≤d+e≤5.40, and preferably 5.15≤d+e is the lower limit of d+e.
[0033] It should be noted that Sm and M in equation (1), as described above, are effective elements for increasing the equilibrium pressure during hydrogen storage and release, improving the squareness of the PCT curve, and reducing the hysteresis of the PCT curve. However, combining these elements can achieve even better results. In equation (1), c+e is 0.55≤c+e≤1.20, preferably 0.57≤c+e≤1.17.
[0034] The elemental composition of the alloy of the present invention represented by formula (1) can be confirmed by quantitative analysis using an ICP (Inductively Coupled Plasma) analysis device. It should be noted that, in this specification, the alloy referred to as the alloy of the present invention, unless otherwise specified, refers to the alloy composed of elements represented by formula (1).
[0035] The alloy of the present invention may substantially contain unavoidable impurities from raw materials, etc. Examples of unavoidable impurities include, but are not limited to, Pr and Nd. The amount of unavoidable impurities in the alloy of the present invention is 0.5% by mass or less.
[0036] The alloy of the present invention can be obtained, for example, in the form of an alloy casting as described later, but the average grain size of the crystals in the alloy casting is preferably 25 μm to 250 μm, more preferably 40 μm to 230 μm. The average grain size of the crystals can be determined as follows: The alloy casting is embedded in a room-temperature curing resin (e.g., epoxy resin) and cured. Coarse and fine grinding is performed using a wet grinder, and the ground surface is finally finished to a mirror finish to form an alloy cross-section. Next, the alloy cross-section is etched, for example, using a 0.1 M nitric acid aqueous solution. Then, the lengths of the major and minor axes orthogonal at their midpoints are measured for each crystal in the field of view using a polarized light microscope. The grain size of the crystal is taken as "(length of the major axis + length of the minor axis) / 2". The grain size of any three crystals is measured in this way, and their average value is taken as the average grain size. There are no particular limitations on the size of the alloy casting used to measure the crystal grain size; for example, approximately 1 cm can be used. 3 The alloy castings. Alternatively, the crystal grain size can be determined using alloy thin sheets approximately 1 cm square, in which case the average grain size is preferably 25 μm to 250 μm.
[0037] The alloy of the present invention preferably exhibits a hydrogen release pressure P at a hydrogen pressure-composition isotherm (PCT curve) of 0.3 wt% hydrogen uptake in a hydrogen uptake amount of 0.3 wt%. a1 Hydrogen release pressure P at a hydrogen uptake of 0.1 wt% a2 Satisfy [{ln(P a1 )-ln(P a2 The relationship is )} / 0.2]≤4.20. This is because, by using the PCT curve with the aforementioned characteristics, the squareness of the curve becomes more pronounced, and more hydrogen can be released when the hydrogen release ends at a predetermined pressure. Therefore, it is possible to produce a very suitable hydrogen storage material that can effectively utilize stored hydrogen without leaving residue in the alloy. More preferably, P a1 and P a2 Satisfy [{ln(Pa1 )-ln(P a2 The relationship is given by )} / 0.2]≤2.00. It should be noted that this relationship is used as an indicator of "squareness". Additionally, when determining the PCT curve, having more than two hydrogen release pressure measurement points between 0.08 wt% and 0.12 wt% of hydrogen uptake is helpful for determining P. a2 It is the preferred option.
[0038] Furthermore, the alloy of the present invention preferably exhibits a hydrogen release pressure P at a hydrogen storage capacity of 0.3 wt% in the hydrogen pressure-composition isotherm at -20°C. a1 Hydrogen release pressure P at a hydrogen uptake of 1.1 wt%. a3 Satisfy [{ln(P a3 )-ln(P a1 The relation that )} / 0.8]≤0.50 is more preferably satisfied with [{ln(P a3 )-ln(P a1 The relationship is given by )} / 0.8]≤0.28. This is because, in the release curve of the PCT curve, the relationship between hydrogen release pressure and the above equation satisfies the above equation. At the hydrogen supply destination, it is easy to maintain the required hydrogen pressure, which has the advantage of ensuring as much usable hydrogen as possible. It should be noted that the above equation is used as an indicator of the "plateau flatness during hydrogen release".
[0039] Furthermore, the alloy of the present invention preferably exhibits a hydrogen absorption pressure P at a hydrogen absorption capacity of 0.8 wt% in the hydrogen pressure-composition isotherm at -20°C. b1 and hydrogen release pressure P b2 Satisfy ln(P) b1 / P b2 The relationship is defined as follows: The relationship between hydrogen uptake pressure and hydrogen release pressure is ≤0.60. In the PCT curve, by ensuring that the relationship between hydrogen uptake pressure and hydrogen release pressure satisfies the above formula, the hysteresis is small. Therefore, a large pressure or temperature difference is not required between hydrogen uptake and release, enabling high-efficiency operation. It should be noted that the above relationship is used as an indicator of the "hysteresis of the PCT curve".
[0040] Furthermore, the alloy of the present invention preferably exhibits a hydrogen release pressure P at a hydrogen storage capacity of 0.8 wt% in the hydrogen pressure-composition isotherm at -20°C. b2 The pressure is 0.05 MPa or higher, more preferably 0.10 MPa or higher. This is because hydrogen release becomes favorable in the temperature range of -20°C to 0°C. For P b2 There is no specific upper limit, but at -20°C it is actually about 4.00 MPa.
[0041] The alloys constituting the hydrogen storage material of the present invention are particularly preferably all satisfied by the above-described relationships in the PCT curve, but it is also possible for only a portion of the alloy to satisfy the above-described relationships.
[0042] Next, the method for manufacturing the hydrogen storage material of the present invention will be described. First, regarding the method for preparing the alloy, examples include strip casting methods such as the single-roll casting, twin-roll casting, or disc casting, as well as metal mold casting.
[0043] For example, in strip casting, raw materials are prepared to form the desired alloy composition. Then, under an inert gas atmosphere such as Ar, the prepared raw materials are heated and melted to form an alloy melt. This alloy melt is then poured onto a water-cooled copper roller for rapid cooling and solidification, thereby obtaining an alloy casting. Similarly, in metal mold casting, an alloy melt is obtained through the same process, and then poured into a water-cooled copper mold for cooling and solidification, thereby obtaining an ingot. The cooling rates differ between strip casting and metal mold casting; generally, strip casting is preferred when an alloy with less segregation and a uniform composition distribution is obtained. The alloy constituting the hydrogen storage material of this invention is preferably an alloy with less segregation and a uniform composition distribution; therefore, strip casting is the preferred method in this invention.
[0044] However, the cooling rate of the alloy molten material during the manufacture of the alloy casting is controlled in the following manner: The cooling rate of the alloy molten material from the cooling start temperature (e.g., the temperature at which the molten metal contacts the roll) to the alloy temperature reaching 1000°C is set to 300°C / second or higher. This cooling rate is preferably set to 700°C / second or higher, more preferably 1000°C / second or higher, and particularly preferably 4000°C / second or higher. There is no particular upper limit to this cooling rate, but in practice it is approximately 20000°C / second or lower. It should be noted that the cooling start temperature of the alloy molten material varies depending on the alloy composition, but is in the range of approximately 1300°C to approximately 1500°C.
[0045] There are no particular restrictions on the cooling rate below 1000°C. For example, in the case of strip casting, after being stripped from the roll, the alloy casting can be recycled by natural cooling, for example, by bringing the temperature of the alloy casting below 100°C.
[0046] Furthermore, in order to form an alloy with a more uniform composition distribution, the alloy casting obtained by the above cooling can be heat-treated. The heat treatment can be carried out in an inert gas atmosphere such as Ar, within a range of 700°C to 1200°C. The heat treatment temperature is preferably 950°C to 1150°C, and the heat treatment time is 1 hour to less than 24 hours, preferably 3 hours to less than 15 hours.
[0047] Next, the alloy casting obtained by casting is pulverized to obtain alloy powder. Pulverization can be carried out using a known pulverizer. The particle size of the alloy powder is preferably 1000 μm or less, more preferably 500 μm or less. It is not necessary to specify a lower limit for the particle size of the alloy powder, but it is essentially about 0.1 μm. Here, the particle size of the alloy powder refers to the diameter measured using a shaking sieve (Rotaup type).
[0048] The hydrogen storage material of the present invention can be the alloy itself obtained by powdering, or it can be a composite material formed by mixing alloy powder and resin, etc., into granules or other arbitrary shapes, or immobilized into a temperature-controllable composite material. In this case, the resin functions as a binder for the alloy powder. Mixing can be carried out by known methods. For example, mixing can be performed using a mortar and pestle, or using a rotary mixer such as a double cone type or V-type mixer, or a stirring mixer such as a blade type or screw type mixer. Alternatively, a pulverizer such as a ball mill or grinding mill can be used to mix the alloy castings and binder while pulverizing them.
[0049] The hydrogen storage container of the present invention has a hydrogen storage material manufactured in the manner described above, and the material and shape of the container can be manufactured in a known manner.
[0050] The hydrogen supply device of the present invention has the above-described hydrogen storage container, and other configurations may be made in a known manner.
[0051] [Example]
[0052] The present invention will now be described in detail through examples and comparative examples, but the present invention is not limited thereto. It should be noted that in the description of these examples, the alloys of the present invention in the examples and the alloys other than those of the present invention in the comparative examples are all referred to as "alloys". Furthermore, the alloy obtained in the form of a cast sheet by continuous casting is called an alloy casting, and the material obtained by pulverizing the alloy casting is called alloy powder.
[0053] (Example 1)
[0054] The raw metal was weighed to achieve the elemental composition shown in Table 1 of the final alloy. This alloy was then melted in an argon (Ar) atmosphere using a high-frequency melting furnace to produce a molten alloy. Next, the casting temperature of this molten alloy was set to 1500°C, and it was rapidly cooled and solidified using a strip casting method with a single-roll casting device employing copper water-cooled rollers, resulting in an alloy sheet with an average thickness of approximately 0.3 mm. The initial cooling temperature of the alloy molten alloy, i.e., the temperature at the moment of contact with the copper water-cooled rollers, was approximately 1450°C. The cooling rate differed between the roller-contact and non-contact sides of the alloy molten alloy, ranging from 6000°C / s to 9000°C / s from 1450°C to 1000°C.
[0055] The alloy casting obtained above was heat-treated in a heat treatment furnace at 1030°C for 10 hours in an Ar atmosphere. The heat-treated alloy casting was then embedded in epoxy resin and cured. Coarse and fine grinding were performed using a wet grinder, and the ground surface was finally polished to a mirror finish to form the alloy cross-section. The alloy cross-section was etched using a 0.1M nitric acid aqueous solution, and the average grain size of the crystals was measured using a polarized light microscope (manufactured by Olympus Corporation) according to the above method. The average grain size was 93 μm.
[0056] In addition, the heat-treated alloy castings were crushed using a stainless steel mortar and sieve with a mesh size of 500 μm, and alloy powder that passed through the 500 μm sieve was obtained.
[0057] The hydrogen absorption and release characteristics of the alloy powder were determined using an automated high-pressure sievet apparatus (manufactured by Hughes Technonet Co., Ltd.), and PCT curves were obtained. Before measurement, the system was first evacuated at 80°C for 1 hour, then pressurized with approximately 2.5 MPa of hydrogen, and finally absorbed hydrogen at -20°C until the hydrogen pressure stabilized. Next, the system was evacuated at 80°C for 0.5 hours, then pressurized with approximately 2.5 MPa of hydrogen, and finally absorbed hydrogen at -20°C until the hydrogen pressure stabilized. This operation was repeated twice for activation. Then, the system was evacuated at 80°C, and the hydrogen pressure was varied between 0.01 MPa and 2.0 MPa at -20°C. The equilibrium pressures for hydrogen absorption and release (hydrogen absorption pressure and hydrogen release pressure) were measured. Figure 1 The figure shows the hydrogen pressure-composition isotherm (PCT curve).
[0058] The difference between the hydrogen uptake at equilibrium pressure of 2.0 MPa and the hydrogen uptake at equilibrium pressure of 0.1 MPa, i.e. the effective hydrogen amount, and the hydrogen release pressure at a hydrogen uptake of 0.8 wt% were read from the release curve of the obtained PCT curve. The results are shown in Table 1.
[0059] As an indicator of the squareness of the PCT curve, the release pressure P at a hydrogen uptake of 0.3 wt% was read from the PCT curve. a1 Release pressure P at a hydrogen uptake of 0.1 wt%. a2 The value of {ln(P)} is calculated. a1 )-ln(P a2 The value obtained by dividing 0.2 by 0.2 is shown in Table 1.
[0060] As an indicator of the plateau flatness (during hydrogen release) of the PCT curve, the release pressure P at a hydrogen uptake of 0.3 wt% was read from the PCT curve. a1 Release pressure P at a hydrogen uptake of 1.1 wt%. a3The value of {ln(P)} is calculated. a3 )-ln(P a1 The value obtained by dividing 0.8 by 0.8 is shown in Table 1.
[0061] As an indicator of the hysteresis of the PCT curve, the adsorption pressure P at a hydrogen uptake of 0.8 wt% was read from the PCT curve. b1 Release pressure P at a hydrogen uptake of 0.8 wt% b2 The value of ln(P) is calculated. b1 / P b2 The values obtained are shown in Table 1.
[0062] (Examples 2-8, 10-23)
[0063] Except for altering the elemental composition of the final alloys as shown in Table 1, alloy castings and powders for each example were prepared in the same manner as in Example 1, and hydrogen storage and release characteristics (squareness, etc.) were measured. The casting temperature, cooling start temperature, and cooling rate of the alloy melts in these examples were approximately the same as in Example 1, ranging from 1500°C, 1450°C, and 6000°C / s to 9000°C / s. It should be noted that in Examples 11, 17, and 18, the hydrogen pressure was varied between 0.01 MPa and 3.0 MPa, and in Example 12, the hydrogen pressure was varied between 0.01 MPa and 4.0 MPa, and the equilibrium pressures for hydrogen storage and release (hydrogen storage pressure and hydrogen release pressure) were measured. The effective hydrogen content in Examples 2-8, 10, 13-16, and 23 was set in the same manner as in Example 1, as the difference between the hydrogen storage amount at an equilibrium pressure of 2.0 MPa and the hydrogen storage amount at an equilibrium pressure of 0.1 MPa. The effective hydrogen content in Examples 11, 17, and 18 was set as the difference between the hydrogen uptake at an equilibrium pressure of 3.0 MPa and the hydrogen uptake at an equilibrium pressure of 0.1 MPa. The effective hydrogen content in Example 12 was set as the difference between the hydrogen uptake at an equilibrium pressure of 4.0 MPa and the hydrogen uptake at an equilibrium pressure of 0.1 MPa. The effective hydrogen content in Examples 19–22 was set as the difference between the hydrogen uptake at an equilibrium pressure of 2.0 MPa and the hydrogen uptake at an equilibrium pressure of 0.01 MPa. The results of the various measurements are shown in Table 1.
[0064] (Example 9)
[0065] Except for not performing heat treatment after alloy casting, alloy castings and alloy powders were prepared in the same manner as in Example 2, and hydrogen absorption and release characteristics (squareness, etc.) were measured. The pouring temperature, cooling start temperature, and cooling rate of the alloy melt in Example 9 were approximately the same as in Example 1, ranging from 1500°C, 1450°C, and 6000°C / s to 9000°C / s. The results of various measurements are shown in Table 1.
[0066] (Comparative Examples 1-5)
[0067] Except for altering the elemental composition of the final alloys as shown in Table 1, alloy castings and powders for each comparative example were prepared in the same manner as in Example 1, and hydrogen storage and release characteristics (squareness, etc.) were measured. The casting temperature, cooling start temperature, and cooling rate of the alloy melts for these comparative examples were approximately the same as in Example 1, ranging from 1500°C, 1450°C, and 6000°C / s to 9000°C / s. The results of various measurements are shown in Table 1. In Comparative Example 2, the hydrogen storage capacity did not reach 1.1% by weight during PCT curve measurement, therefore the plateau flatness could not be calculated. The hydrogen pressure-composition isotherm (PCT curve) of Comparative Example 1 is shown in Table 1. Figure 1 In addition, the hydrogen pressure-composition isotherm (PCT curve) of Comparative Example 3 is shown in... Figure 2 middle.
[0068]
[0069] As clearly shown in the table, compared with the alloys of the comparative examples, the alloys of each embodiment exhibit good squareness in their PCT curves, demonstrating sufficient hydrogen storage capacity. Furthermore, the hydrogen release pressure at a hydrogen storage capacity of 0.8% by weight is consistently above 0.05 MPa, indicating sufficient hydrogen storage and release within a temperature range below 0°C. Moreover, it is evident that an excellent hydrogen storage material with low hysteresis in its PCT curve can be obtained.
Claims
1. A hydrogen storage material, wherein, The hydrogen storage material has an alloy composed of the composition represented by the following formula (1). In formula (1), M is at least one selected from Mn, Co, and Al and must include Mn; a is 0.00≤a≤0.62; b is 0.20≤b≤0.57; c is 0.17≤c≤0.60; d is 4.50≤d≤5.20; e is 0.15≤e≤0.70; a+b+c=1; c+e is 0.55≤c+e≤1.20; and d+e is 5.13≤d+e≤5.
40. In the hydrogen pressure-composition isotherm diagram of the alloy at -20°C, the hydrogen release pressure P at a hydrogen uptake of 0.3 wt% is... a1 Hydrogen release pressure P at a hydrogen uptake of 0.1 wt% a2 Satisfy [{ln(P a1 )-ln(P a2 The relation is )} / 0.2]≤4.
20.
2. The hydrogen storage material as described in claim 1, wherein, In the above formula (1), M is Mn or both Mn and Co, a is 0.00≤a≤0.40 and c is 0.20≤c≤0.
60.
3. The hydrogen storage material as described in claim 1 or 2, wherein, The P a1 and the P a2 Satisfy [{ln(P a1 )-ln(P a2 The relation is )} / 0.2]≤2.
00.
4. A hydrogen storage container, wherein, The hydrogen storage container has the hydrogen storage material as described in any one of claims 1 to 3.
5. A hydrogen supply device, wherein, The hydrogen supply device has the hydrogen storage container as described in claim 4.
Citation Information
Patent Citations
Hydrogen storing material
JP1985070154A
Hydrogen storage material
JP1988047345A
Hydrogen storage alloy composition, and electrode for nickel-hydrogen storage battery
JP1998183280A